Precise Large Deviations of Aggregate Claims with Dominated Variation in Dependent Multi-Risk Models - Shijie Wang; Xuejun Wang; Wensheng Wang (Abstract and Applied Analysis)
We consider a dependent multirisk model in insurance, where all the claims constitute a linearly extended negatively orthant dependent (LENOD) random array, and then upper and lower bounds for precise large deviations of nonrandom and random sums of random variables with dominated variation are investigated. The obtained results extend some related existing ones.